Integration of SDGS into Presentation Skills: Sharing Practice by LMD - Ab Hamid, Ahmad Rauyani; Ali, Mohd Aizat (2021)
Since 2018, the University has vigorously geared its direction towards Sustainable Development Goals (SDGs). With the introduction of Sejahtera Academic Framework (SAF) in 2020, the University expects all KCDIOs to manifest it in their practices. Echoing this, the Department of Languages and Management (LMD) agreed to include SDG elements in one of the assessments of its new subject, Presentation Skills. The students were tasked to choose one of SDGs for their group presentation. The main objective of this poster is to share some insights gained from the previous semester when SDGs are concerned. To do so, we plan to 1) analyse overall student performance across the four programs under LMD, 2) find out the common SDG topics selected by students and perhaps to 3) have the teaching staff share their experiences.